2019
DOI: 10.1159/000504312
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns for the Treatment of Uveal Melanoma with Iodine-125 Plaque Brachytherapy: Ocular Oncology Study Consortium Report 5

Abstract: Background: Treatment planning for I-125 plaque therapy for uveal melanoma has advanced significantly since the Collaborative Ocular Melanoma Study trial, with more widely available image-guided planning and improved dosimetry. Objective: We evaluated real-world practice patterns for I-125 plaque brachytherapy in the United States by studying practice patterns at centers that comprise the Ocular Oncology Study Consortium (OOSC). Methods: The OOSC database and responses to a treatment practice survey were eval-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We therefore cannot draw conclusions about survival or the incidence of metastatic melanoma between patients treated with RAI and PBT. The literature, however, does not document a difference in survival or the likelihood of liver metastases from UM in patients treated with RAI 27 , 28 , 29 or PBT. 30 , 31 , 32 , 33 Also, one randomized clinical trial compared helium ion radiation to radioactive iodine implant 22 and found no significant difference in survival.…”
Section: Discussionmentioning
confidence: 93%
“…We therefore cannot draw conclusions about survival or the incidence of metastatic melanoma between patients treated with RAI and PBT. The literature, however, does not document a difference in survival or the likelihood of liver metastases from UM in patients treated with RAI 27 , 28 , 29 or PBT. 30 , 31 , 32 , 33 Also, one randomized clinical trial compared helium ion radiation to radioactive iodine implant 22 and found no significant difference in survival.…”
Section: Discussionmentioning
confidence: 93%
“…We suspect that the increased utilization of EPBT for large tumors is due to the advancements in EPBT technology, such as custom plaque designs, intra-operative optimization of plaque positioning using ultrasound, and developments in EPBT treatment planning systems [ 5 , 22 , 23 ]. The COMS trial evaluating EPBT excluded tumors of > 16 mm in basal diameter because the eye-plaques available at that time were not big enough to cover tumors larger than this.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, methods such as brachytherapy (iodine-125, ruthenium-106, palladium-103, or cesium-131 plaque brachytherapy), proton beam radiotherapy, stereotac-tic irradiation or radiation surgery (LINAC, Gamma Knife, CyberKnife), transcleral local resection, transretinal resection, vitreoretinal (VR) surgery, and diode laser phototherapy have taken precedence. Radiotherapy, phototherapy, and local tumor resection are also often used in combination [5,[27][28][29][30]. Radiation therapy is currently the most used technique for the treatment of UM, with brachytherapy isotope plaques emitting gamma radiation being used in most ophthalmology centers [31,32].…”
Section: Current Therapy Of Ummentioning
confidence: 99%